Avaliação da eficiência do revestimento anticorrosivo à base de diacetato de celulose para aço API 5L X65 - Nunes, Letícia Danielli Coelho (2023)
One of the main causes of accidents that culminate in oil spills is the corrosion of pipelines, both during transport and storage. The most used way to contain the corrosion of these tubes is the use of anticorrosive coatings. This choice is due to the fact that they are economical and do not re-quire frequent maintenance. However, the coatings available on the market are generally toxic and aggressive to humans and the environment. The use of organic coatings has become highly rele-vant, as it leads to the discussion of the use of environmentally friendly coatings, prepared from raw materials from renewable sources, safer, compatible with the natural ecosystem and more accessible. The objective of this work was to prepare and evaluate the corrosion protection effec-tiveness of API X65 steels coated with polymeric films of cellulose diacetate, methyl polymeth-acrylate and PAN-PVA co-polymer in a 3.5% NaCl aqueous solution. The steels coated with dif-ferent polymers were electrochemically characterized by the graph of stabilized Open Circuit Po-tential (OCP), polarization curves and electrochemical impedance spectroscopy. In addition to these, structural characterizations by Fourier transformed infrared spectroscopy (FTIR) and mor-phological characterizations by Scanning Electron Microscopy (SEM) were performed. The SEM images showed that the anticorrosive coating based on PAN-PVA co-polymer presented the most compact morphology among the investigated polymeric films. The electrochemical characteriza-tions showed that the studied coatings provoke a displacement of the corrosion potential of the steel towards more positive values and a significant decrease in the values of the corrosion current density, mainly for the steels containing the films of PMMA and of the co-polymer PAN- PVA. Among the polymeric films investigated as anticorrosive coatings, cellulose diacetate is the bio-degradable and the most ecologically correct, so this was analyzed by EIE over the immersion time in NaCl 3.5%. Steels coated with four layers of DAC had high percentages of anticorrosion efficiency in different immersion times. The loss of corrosion protection efficiency over the im-mersion time of 2304 hours was not significant, maintaining a value around 99% in the saline me-dium. So, anticorrosive coatings based on cellulose diacetate are promising and more compatible with the natural ecosystem.